2016
DOI: 10.5194/acp-16-1065-2016
|View full text |Cite
|
Sign up to set email alerts
|

The importance of temporal collocation for the evaluation of aerosol models with observations

Abstract: Abstract. It is often implicitly assumed that over suitably long periods the mean of observations and models should be comparable, even if they have different temporal sampling. We assess the errors incurred due to ignoring temporal sampling and show that they are of similar magnitude as (but smaller than) actual model errors (20-60 %).Using temporal sampling from remote-sensing data sets, the satellite imager MODIS (MODerate resolution Imaging Spectroradiometer) and the ground-based sun photometer network AER… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…Although statistical profile results (e.g., Turner et al, 2001;Yu et al, 2010;Ma and Yu, 2014) suggest little contribution from high-altitude aerosol layers in the region of these two sites, Schutgens et al (2016) demonstrate the importance of considering the specifics rather than the statistical. We used the Raman lidar best-estimate data product of extinction profiles at SGP to evaluate the presence of aerosol above the highest flight level at the site.…”
Section: E Andrews Et Al: Comparison Of Aod Aaod and Column Singlementioning
confidence: 99%
See 1 more Smart Citation
“…Although statistical profile results (e.g., Turner et al, 2001;Yu et al, 2010;Ma and Yu, 2014) suggest little contribution from high-altitude aerosol layers in the region of these two sites, Schutgens et al (2016) demonstrate the importance of considering the specifics rather than the statistical. We used the Raman lidar best-estimate data product of extinction profiles at SGP to evaluate the presence of aerosol above the highest flight level at the site.…”
Section: E Andrews Et Al: Comparison Of Aod Aaod and Column Singlementioning
confidence: 99%
“…The low number of flights for which there are comparisons available (∼ 10 % of total number of flights) indicates both the effects of AERONET's stringent cloud screening routine and the constraints imposed by the almucantar retrievals. In addition to limiting the number of comparisons available for this study, this limited data availability also has implications for modellers utilizing AERONET data -for example, Schutgens et al (2016) showed the importance of temporal collocation in measurement-model comparisons. Figure 4 also contains red points -the red data points represent all directsun AERONET Level 2 AOD measurements during the ±3 h window around the end of each profile.…”
Section: Bnd and Sgp: In Situ Vs Aeronet -Direct Comparisonsmentioning
confidence: 99%
“…A strong caveat in these comparisons is that the modelled AOD has not been sampled with the spatial and temporal incidence of the MODIS data. Schutgens et al (2016) showed that this can result in considerable regional biases between modelled and observed monthly and annual mean AOD. In particular, the comparison may be of limited value at high latitudes (beyond 60 • N or S) where retrievals are not possible for several months of the year (due to the solar zenith angle being too high, or due to a lack of solar illumination altogether).…”
Section: Averaging Methodsmentioning
confidence: 99%
“…Whilst these results give clues as to where BB aerosol emissions may be overestimated or underestimated, the differences between modelled and observed AOD may be affected by various other sources of uncertainty in the models and measurements. In particular, temporal sampling biases may affect the results (Schutgens et al, 2016), as we have not sampled the model data to match AERONET retrieval times. The approach we have taken is to average over 10 years of data to gain more confidence in the long-term monthly means.…”
Section: Aod Comparison With Aeronetmentioning
confidence: 99%
“…While the data we use from CALIOP are spatially collocated with the AERONET stations and model data, it is not temporally collocated. A recent study has shown that temporal collocation can be significant, and sampling errors are introduced when it is not considered (Schutgens et al, 2016).…”
Section: Caliopmentioning
confidence: 99%